QUALITY ASSURANCE OF SMALL VOLUME PARENTERAL PRODUCT WITH QUALITY BY DESIGN APPROACH: A REVIEW - Ramadhani, Anietta Indri Nur; Yuliana, Sri; Sulaiman, Teuku Nanda Saifullah (Journal Pharmaceutical Science and Application; Vol 6 No 2 (2024): Journal Pharmaceutical Science and Application ; And IMPORTANT ANNOUNCEMENTDO - 10.24843/JPSA.2024.v06.i02.p02, 2025)
Background: Nowadays, many small-volume injection products are circulating on the market. Small-volume parenteral (SVP) products are usually designed for treatment purposes that provide systemic effects. If it is not produced strictly, the product will be hazardous and even life-threatening. Quality assurance is one of the primary tools used to ensure the acceptable performance of SVP products. Quality by design (QbD) represents a systematic strategy for product development that starts with setting a target product quality and emphasizes product process control based on a scientific approach and quality risk assessment. The purpose is to ensure SVP product quality from design to production process. Objective: This review will determine generally Critical Quality Attributes (CQA), Critical Material Attributes (CMA), and Critical Process Parameters (CPP) in terms of explaining the quality assurance of SVP products with a quality-by-design approach. Methods: All articles were obtained by electronic search using ICH guidelines, Science Direct, and Google Scholar. Results: From the literature review, it was found that using a quality-by-design approach through integrated CQA, CMA, and CPP can produce SVP products that comply with QTPP (Quality Target Product Profile) and regulatory requirements. Conclusion: QbD has been established as a valuable scientific approach for ensuring quality assurance within the pharmaceutical industry. Pharmaceutical companies prioritize obtaining regulatory approval before introducing any product to the market. Keywords: Critical Process Parameter; Critical Quality Attributes; Quality by Design; Parenteral; Small Volume Parenteral.